Beyond COVID-19: a cross-sectional study in Italy exploring the Covid Collateral Impacts. (30th September 2020) - Gualano, M R; Corradi, A; Voglino, G; Bert, F; Siliquini, R
Abstract: Background: The COVID-19 pandemic is a calamity affecting many aspects. In particular healthcare services (HCS) are facing a great stress-test worldwide. The present work aims to explore what were health needs, beyond COVID, not covered among Italian citizens, due to fear, lockdown measures and overload of HCS, also in order to understand if there are specific subgroups of populations that will need urgent access to health services in the next future. Methods: COCOS (COvid COllateral impactS) is a cross-sectional study performed during the Italian lockdown between April and May 2020. A forty-nine items online questionnaire was filled by the respondents. Participation was voluntary and without compensation. Informed consents were obtained. Descriptive, univariable and multivariable (logistic regression models) analyses were performed: results are expressed in ORs. Results: Totally, 1, 515 questionnaires were collected. Median age was 42 years, 65.6% were females. Around 22% declared to suffer from chronic diseases. Interestingly, 32.4% of the sample faced a delay of a scheduled Medical Service (MS) by provider decision, while 25.6% reported that this issue hit a family member. More than 13% refused to access scheduled MS for the fear of contagion, and the 6.5% avoided HCS even if having an acute onset issue: this behavior was associated with scarce trust in physicians (AdjOR 0.75); alarmingly, 1.5% avoided Emergency Department when in need and 5% of the sample took medications without consulting any physician: patients suffering from chronic conditions resulted to be more prone to self-medication (AdjOR: 2.16; 95% C.I.: 1.16-4.02). Conclusions: COVID-19 immediate effects are just the tip of the iceberg. Large groups of population suffered delays and interruptions of medical services, and the most vulnerable were the most affected. To estimate the effects of the pandemic on non-COVID-19 patients is required, leading to aimed efforts, to reduce the backlog that HCS incurred in. Key messages: COVID-19 biggest toll on public health is still to come if not prevented, due to temporary but widespread suspensions of scheduled medical services and the avoidance of these for fear of contagion. The most in need are the most vulnerable: older patients and those with chronic conditions are the most affected by suspension of medical services and will potentially pay the greatest cost.